Development of physic learning video properties of light with colaboration teacher and student as learning media in new normal era - Fita Permata Sari; Dee Dee Mahmood; Salamun Hadi Subroto; Puji Iman Nursuhud; Herry Prasetyo (Universitas Sultan Ageng Tirtayasa, 2022)
The era of digital technology is very influential on education in the new normal era covid-19 pandemic. The making of physics learning videos can be applied with the collaboration of teachers and students. This research aims to produce the physic learning video properties of light with teacher and student as learning media in new normal era. This Research and Development (R & D) began with preliminary research, research design, developing initial products, limited test trials, revision of limited trials, initial field trials, and revision of initial field trials. The research was applied to 8th grade junior high school students while learning Science Physics Chapter of the Properties of Light. This research used instruments are questionnaires. The product is in a good category so that it is feasible to be used and implemented in the physics science learning process in the new normal era.